Strong context-dependent virulence in a host-parasite system: reconciling genetic evidence with theory - BROWN, MARK (Blackwell, 2003)
1. Parasites can have dramatic effects on the ecology of their hosts. Such strong host-parasite interactions are the result of either parasites with generally high virulence, or generally benign parasites that nevertheless express context-dependent virulence. Theoretically, one indication that an apparently benign parasite nevertheless has a large impact on its host should be the existence of strong genotypic interactions between host and parasite. 2. Crithidia bombi (Trypanosomatidae) is a highly prevalent but generally benign gut parasite of the bumble bee Bombus terrestris. The demonstration of strong genotypic interactions between C. bombi and B. terrestris, however, suggests that context-dependent virulence may have a large impact on the host population. We thus investigated the effects of C. bombi across the entire life-cycle of its host, including the stressful times of hibernation and colony-founding. Due to the high prevalence and rates of transmission of the parasite in field populations, we used a large-scale laboratory experiment. 3. Under stressful hibernation, infected queens lost more weight. Infection also significantly reduced colony-founding success, colony size, male production and overall fitness, by up to 40%. These findings show that strong genotypic host-parasite interactions may indeed be a reliable indicator that apparently benign and highly prevalent parasites are nevertheless exerting a dramatic impact on their host populations.
PUBLISHED
Keywords: Zoology